Fire activity over Mediterranean Europe based on information from Meteosat-8 - Amraoui, Malik; Liberato, Margarida L.R.; Calado, Teresa J.; DaCamara, Carlos C.; Coelho, Luís Pinto; Trigo, Ricardo M.; Gouveia, Célia M. (Forest ecology and management, 2013)
► We study fire activity over Mediterranean Europe based on data from Meteosat-8. ► We assess the role played by land cover and by weather conditions on fire events. ► The vast majority of persistent fire events occur in forest and shrub. ► We propose a conceptual model for weather conditions favouring severe fire events. ► Results pave the way to the generation of daily calibrated maps of fire risk. Mediterranean regions are some of the most affected by wildfires and remote-sensed information about fire activity, as provided by the SEVIRI instrument on-board Meteosat-8, is especially valuable for forest and civil protection activities. An analysis is performed of the spatial distribution of fire events during the period of July and August 2007–2009. Around half of fire pixels were detected in croplands, the remaining half being evenly distributed between forest and shrub, as opposed to the distribution of persistent fire events (more than 10h of duration) where 90% occurred in forest and shrub, evenly distributed between these two classes. With slightly more than half of the fire events and the most severe episodes, the year of 2007 is the most serious, allowing an assessment of the role of meteorological conditions on large fire events based on the analysis of low, mid and upper atmospheric fields of geopotential, temperature, relative humidity and wind. The analysis of two extreme events of fire activity that struck Greece and Italy on 24–25 July and 22–27 August, 2007 suggested a conceptual model for meteorological conditions favouring the occurrence of severe wildfire episodes in Italy and the Balkan Peninsula. On the one hand there is, at the surface, strong northerly advection of very hot and very dry air over the region, as steered by the presence of a ridge over central Europe together with a thermal depression over southwest Asia. On the other hand, the air advected is further heated by adiabatic compression associated to strong subsidence from around 700 up to 250hPa, associated to the presence of a ridge over the Eastern Mediterranean and to the anomalous displacement of the jet streak towards the northwest. The importance of both short- and long-term atmospheric conditions on meteorological fire risk is also put into evidence by analyzing the fields of three weather-based indices, namely the Build-Up Index, the Initial Spread Index and the Fire Weather Index that are part of the Canadian Forest Fire Weather Index System. Identified links of fire onset and fire persistence with land cover types and with atmospheric circulation patterns suggest using data on fire activity as derived from Meteosat-8/SEVIRI to generate statistically calibrated maps of fire risk in Mediterranean Europe.